KEPATUHAN MINUM OBAT PADA PASIEN DIABETES MELITUS TIPE 2. APAKAH EFIKASI DIRI BERPENGARUH? - Mawaddah, Mawaddah; Ulfa, Maria; Fredy Saputra, M. Khalid; Wirda, Wirda (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Diabetes mellitus (DM) is a chronic condition characterized by elevated blood glucose levels or hyperglycemia resulting from impaired insulin secretion, decreased sensitivity to insulin, or a combination of both. Based on preliminary studies conducted at the Sindang Barang Community Health Center, it was found that some patients with type 2 diabetes mellitus still experience problems with adherence to treatment. The purpose of this study was to determine the relationship between self-efficacy and medication adherence in patients with type 2 diabetes mellitus. A cross-sectional study design was used in this study. The study was conducted in the working area of the Sindang Barang Community Health Center. The study was conducted in February 2025. The population consisted of Type 2 Diabetes Mellitus patients at the Sindang Barang Community Health Center in Bogor. The research sample consisted of 88 respondents. The sampling technique used was purposive sampling. The research instrument used was a research questionnaire. Data analysis was performed using univariate and bivariate methods. The results showed a relationship between self-efficacy (p value: 0.002) and medication adherence in patients with type 2 diabetes mellitus. It is recommended that the Sindang Barang Community Health Center in Bogor create broader communication between diabetes mellitus patients, their families, and health workers so that good medication adherence can be achieved in patients with type 2 DM. Keywords: Self-efficacy, Diabetes, Compliance.